2017
DOI: 10.1101/168021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cross-validation-based approach for delimiting reliable home range estimates

Abstract: Background With decreasing costs of GPS telemetry devices, data repositories of animal movement paths are increasing almost exponentially in size. A series of complex statistical tools have been developed in conjunction with this increase in data. Each of these methods offers certain improvements over previously proposed methods, but each has certain assumptions or shortcomings that make its general application difficult. In the case of the recently developed Time Local Convex Hull (T-LoCoH) method, the subjec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Two such metrics are the duration of a visit to a particular point or area of interest, known as the residence time, and the rate at which individuals return to them, known as the visitation or return rate. Used together, these metrics can offer a means of evaluating the relative risk of contact or exposure among individuals (Dougherty et al 2017). Site-fidelity metrics such as these could be particularly important in the case of indirectly transmitted pathogens because high levels of fidelity increase exposure risk if an infectious reservoir is present in the range but will buffer an individual from exposure if the range is free of relevant pathogens or parasites.…”
Section: Indirect Transmissionmentioning
confidence: 99%
“…Two such metrics are the duration of a visit to a particular point or area of interest, known as the residence time, and the rate at which individuals return to them, known as the visitation or return rate. Used together, these metrics can offer a means of evaluating the relative risk of contact or exposure among individuals (Dougherty et al 2017). Site-fidelity metrics such as these could be particularly important in the case of indirectly transmitted pathogens because high levels of fidelity increase exposure risk if an infectious reservoir is present in the range but will buffer an individual from exposure if the range is free of relevant pathogens or parasites.…”
Section: Indirect Transmissionmentioning
confidence: 99%
“…Note how previous conclusions on the influence of autocorrelation on home range estimation were based on weakly autocorrelated data that are not representative of the majority of modern GPS data. while others have simply shown empirical results without reference to their accuracy (e.g., De Solla et al 1999, Dougherty et al 2017. In the absence of the latter, researchers have been encouraged to obtain a threshold number of locations (Seaman et al 1999, Girard et al 2002) or days (e.g., B€ orger et al 2006, but the precise conditions under which autocorrelation and movement behavior can a priori be expected to influence these thresholds have remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, interspecific variation in movement still requires investigation, given the wealth of movement data collected in Etosha over the past two decades (Lyons, Turner & Getz, 2013;Mashintonio et al, 2014;Polansky, Kilian & Wittemyer, 2015;Dougherty et al, 2017Dougherty et al, , 2018aZidon et al, 2017); for example, elephants largely migrate away from the known anthrax areas of Etosha during the anthrax season, and return in the dry season. Intraspecific variation also requires further investigation; evidence suggests that there may be a link between partial migration of zebra herds in Etosha and avoidance of the anthrax season.…”
Section: (4) Ecologymentioning
confidence: 99%
“…It has been suggested that this phenomenon could be linked to dominance structure, as dominant groups migrate, while resident (submissive) herds are encouraged to stay by decreased competition (Zidon et al, 2017). Movement data from Etosha has already been used to help develop anthrax-relevant analytic tools (Dougherty et al, 2017) and simulations (Dougherty et al, 2018a), and while some work in other systems has used movement data and tools to help map the link between environmental suitability and host exposure (Morris et al, 2016), similar work is still needed in Etosha [as it is needed in any system with the potential for transmission at the wildlife-livestock interface, where these tools are often the most useful for answering applied questions (Dougherty et al, 2018b)].…”
Section: (4) Ecologymentioning
confidence: 99%